A Crazy Day at the Critter Cafe - Barbara Odanaka (New York, United States SIMON & SCHUSTER, 2009)
Swish, zoom, swish. Clickety-clack! When a bus full of critters breaks down, a sleepy roadside café suddenly wakes up! Raccoons, elephants, zebras, and rams are only a few of the many animals demanding grub, and it is all that a cook and a waiter can do to keep up. But when Skateboard Cow swerves her way through the crowd, more than a few feathers are guaranteed to be ruffled! Rhythmic text and energetic illustrations combine for a romp of pure fun and entertainment.
Keywords: Read Aloud -- Read Aloud